THE IMPORTANCE OF HUMOR ELEMENTS IN ISLAMIC DA'WAH MESSAGES AMONG THE MILLENNIAL GENERATION - Luthfi, Muhammad; Karimullah, Suud Sarim; Nugraha, Aat Ruchiat (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2024)
Using humor in Islamic da'wah can effectively approach the millennial generation more engagingly and entertainingly. This study aims to identify factors that need to be considered when using humor in the context of da'wah, especially when dealing with millennials with different characteristics and communication preferences. This study uses a library research method to develop a strong and comprehensive theoretical foundation related to the topic of study. The study's findings show that the application of humor in Islamic da'wah among the millennial generation requires a balanced approach between creativity, ethics, and a deep understanding of the characteristics of the millennial generation, which in turn affects the effectiveness of da'wah. A better understanding of millennials' communication preferences and values can enrich the use of humor to create emotional connections and effectively convey religious messages while ensuring that the messages remain consistent with the values of true Islamic teachings. This study implies that in the face of technological advancements and the social media landscape, humor can be an effective tool for fostering emotional connections with millennial audiences and effectively conveying religious messages, provided that its use is directed toward the positive goals of enriching religious understanding, strengthening communication, and ensuring consistency with Islamic values that are rahmatān lil ‘ālamīn.